Caracterização da cadeia produtiva da pesca associada ao subproduto de "grude" no município de São João de Pirabas, nordeste paraense - SOUZA, Barbara Marques de (2024)
This work focuses on the analysis of the fishing production chain in the municipality of São João de Pirabas, located in the state of Pará, northeast of Pará. The study addresses fishing practices in the coastal waters of the Salgado region and analyzed the dynamics involving the processing and commercialization of the sticky by-product, the associated target species, highlighting the characteristics of the gear and the actors involved in the production chain. The methodology included interviews, field observation and exploratory documentary analysis. The results indicated the diversification of fisheries and that there are activities associated with the production chain to maintain ways of life, such as the commercialization of fishing by-products. The research sought to contribute to an understanding of the relationships involving the marketing of glue and artisanal fishing activity and to understand the cultural and ancestral aspects of fishing activity in local communities.